The effects of corporate governance on stock liquidity: Evidence from Tehran Stock Exchange - Aboubakr Arazpour; Mohammad Esmaeil Fadaeinejad (Management Science Letters)
This study examines the relationship between corporate governance’s mechanisms and liquidity of stocks on 66 selected firms listed on Tehran Stock Exchange over the period 2005-2009. Board composition and ownership structure are used as corporate governance’s mechanisms and illiquidity measure proposed by Amihud (2002) [Amihud, Y. (2002). Illiquidity and stock returns: cross-section and time-series effects. Journal of financial markets, 5(1), 31-56.] is used to measure stock liquidity. The results show that an increase on the number of independent boards is associated with higher liquidity. In addition, the results show that there was a significant relationship between liquidity and ownership structure. In other words, the relationships between liquidity and individual investors and five biggest investors are positive and the relationships between liquidity and institutional ownership and the biggest investor ownership are negative. In addition, there is not a significant relationship between liquidity and duality of managers.